Dark Side of the Web in the Context of Online Radicalization - Erdoğan, Halide (Journal of Islamic Thought and Civilization, 2023)
Radicalization refers to the mental process that legitimizes violence or violent actions under the influence of social, cognitive and economic factors. With the advent of the Internet, radical groups have also changed their methods of action by adapting to the new conjuncture. The Internet is no longer just a part of the spectrum of extremist activities, however, it also become the primary arena and operational environment where political ideologies are shaped, attacks are planned and extraordinary social movements begin to emerge. Group members come together on online platforms to have discussions about faith and use these platforms to expand the spectrum of activism at both individual and organizational levels in order to spread their political ideologies, to recruit staff, and to plan attacks. In the current study, conceptual framework, individual and group dynamic causes of radicalization, metaphors explaining radicalization, religiously motivated radicalization, online radicalization and case examples are emphasized.